Faktor-faktor Yang Mempengaruhi Remitan Migran Nonpermanen Ke Daerah Asal (Studi Kasus: Desa Jimbaran, Kecamatan Kuta Selatan, Kabupaten Badung) - Novayanti, Luh; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 12, Desember 2013 (pp. 547-569), 2013)
Growth is determined by the balance of public welfare so that it appears the phenomenon of remittances to improve the welfare of the people especially in rural. Remittances are money or goods sent/brought by migrant nonpermanent to meet the needs of migrant families left behind in the area of origin. Remittances is due to the kinship ties that bind between migrant and native region. The purpose of this study was determine the factors that determine the amount of remittances that sent/brought to the area of origin by non-permanent migrants. The research conducted in Jimbaran village because the village was visited by many migrants who work in the tourism sector. Data collection methods used is a structured interview and observation with 69 respondents and use of data analysis techniques of multiple linear regression. The results showed that the factors that determine the amount of remittances that brought/sent to the area of Jimbaran village simultaneous origin unknown variable number of dependents, amount of expenditure, frequency of delivery of remittances to the region of origin, and the presence of the nuclear family in the area of origin have a significant effect, whereas in partial number of dependents, the frequency of remittances to the region of origin, and the presence of the nuclear family in the area of origin and the amount of spending has a positive effect and negatively effect the amount of remittances by non-permanents migrants to the area origin, the dominant variable is the number of dependents.
Keywords: Remittances; Migrant Nonpermanent; Amount of Remittances